Climate-Related Development Finance, Energy Structure Transformation and Carbon Emissions Reduction: An Analysis From the Perspective of Developing Countries - Li, Nan; Shi, Beibei; Wu, Lei; Kang, Rong; Gao, Qiang (Frontiers in Environmental Science, 2022)
Considering the differences between developed and developing countries in climate response capacity, a key issue is how to encourage developed countries to provide adequate assistance to developing countries and enhance their enthusiasm to participate in addressing climate change challenges. Given this background, we evaluated the carbon emission reduction effects of developing countries before and after a "quasi-natural experiment" which involved obtaining the assistance of climate-related funding from developed countries. Specifically, we analyzed the assistance behavior for recipient countries and found that climate assistance can effectively reduce the carbon emissions level of recipient countries, and this result has a better impact on non-island types and countries with higher levels of economic development. Furthermore, the achievement of this carbon emissions reduction target stems from the fact that climate assistance has promoted the optimization of the energy structure of recipient countries and promoted the substitution of renewable energy for coal consumption. In addition, climate-related development finance plays a significant role in promoting the scientific and technological level of recipient countries, especially the development impact of the adaptive climate-related development finance. Therefore, this paper suggests that the direction of climate assistance should focus more on island countries and countries with low economic development level, and pay more attention to the "coal withdrawal" of recipient countries and climate adaptation field.